Air Quality Index Prediction with the Implementation of Linear Regression - A Technical Paper - Chakraborty, Soumyajit; Guha, Koustav (International Journal of Computer Sciences and Engineering, 2020)
Within the last few years, an intense curiosity has been progressed by the people in the daily air quality circumstances to which they are encountered. Directed by the growing consciousness of the physical state of air pollution exposure, especially by most sensitive sub–populations such as children and the elderly, short–term air pollution forecasts are being accentuated progressively by local authorities. The Air Quality Index (AQI) is the value implemented to estimate the quality of the air at a certain location. The components are estimated with the implementation of the covariance of the input data matrix.